2020
DOI: 10.1021/acs.organomet.0c00540
|View full text |Cite
|
Sign up to set email alerts
|

Bis(phosphine)cobalt-Catalyzed Highly Regio- and Stereoselective Hydrosilylation of 1,3-Diynes

Abstract: Seven bis­(phosphine) cobalt complexes and one tris­(phosphine) cobalt complex were tested for hydrosilylation of 1,3-diynes, among which dppp-CoCl2 (1 mol %) exhibited the best regio- and stereoselectivity, affording (E)-2-silyl-1,3-enynes through monohydrosilylation at the internal carbon of the 1,3-diyne unit via syn addition. Good functional tolerance was achieved, 32 substrates were tested, and the reactions could be readily amplified to a gram level. For most of the substrates, the transformation could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…( 4)]. [23] Moreover, given that a NHC-CoCl 2 catalyst can efficiently promote this chain-walking process [Eq. ( 5)], a stoichiometric reaction of Co(IMes) 2 Cl 2 , B 2 Pin 2 and NaO t Bu showed the formation of Co(IMes) 2 Cl [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…( 4)]. [23] Moreover, given that a NHC-CoCl 2 catalyst can efficiently promote this chain-walking process [Eq. ( 5)], a stoichiometric reaction of Co(IMes) 2 Cl 2 , B 2 Pin 2 and NaO t Bu showed the formation of Co(IMes) 2 Cl [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous studies, a proposed mechanism is shown in Scheme . Initially, the bisphosphine Co­(II)­Cl 2 complex reacts with NaHBEt 3 to generate the Co­(I)–H intermediate A .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Huang et al discovered a pincer Fe catalyst (2.0 mol %) for hydrosilylation of 4-alkyl-substituted, 1,4-disubstituted, and 1,1,4-trisubstituted 1,3-enynes, and after 12 h at 0 °C, a series of 4,3-adducts were generated (Scheme ). In consideration that Co catalysts are efficient for the selective hydrosilylation of alkynes and conjugated diynes, , we speculated that some of them might also be applied for hydrosilylation of 1,3-enynes. Co complexes based on a bisphosphine ligand can be good choices because many organic diphosphines are commercially available at low prices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Ge and colleagues reported in 2019 the regio-and stereoselective access to a broad range of silylfunctionalized 1,3-enynes by hydrosilylation of 1,3-diynes (syn addition), employing a catalyst generated from bench-stable Co(acac) 2 and 1,3-bis(diphenylphosphino)propane (dppp) (Scheme 29) [72]. Related hydrosilylation reactions, featuring the same regio-and stereocontrol, were subsequently described with other cobalt-based catalytic systems, such as complexes 51 [73] and 52 [74] (see Figure 8) or the CoCl 2 /dppp combination [75]. In these cases, the reducing agent NaHBEt 3 was systematically employed as a co-catalyst, allowing the reactions to proceed under milder conditions (r.t. or 30 • C) and shorter times (from 5 min to 1 h).…”
Section: Hydrosilylation Processesmentioning
confidence: 99%